Property Appraisals: Considerations Regarding the Income Approach - Its use and Possible Distortions in the Leasing Market (Global Journal of Management and Business Research, 2022)
This study analyzes the Income Approach NBR 14653-4 2002 more specifically in item 9 3 when it proposes to identify the value of the enterprise based on the expectation of future results At this point the property valuation protocol has been much discussed especially in some lawsuits due to the confirmed feeling that there is a lack of discretion when using in a mistaken way its dictates in properties not characterized as real estate-based that is that is reaching real estate land and or buildings not produced prepared for the lessor to exploit economically The referred standard adds that the value of the project will correspond to the present value of the projected cash flow discounted at given rates What has been seen is that the widespread use of this approach presupposes that the lessee will use the property attached to an exotic type of partnership with the lessor These valuation procedures disconnected from reality somehow deviate from NBR 14653-2 2011 when the ideal would be to use the Direct Comparative Method of Market Data thus considering the value of the property in relation to the value of the properties similar in a given region
Keywords: property valuation standards series NBR 14653; rent method; real estate based leases; direct comparative market data method